CONTENT OF STUDENT READYNESS FORMATION PEDVUZE TO DIALOGICAL LEARNING - V.V. Morozov (Academy of Cognitive and Natural Sciences, 2004)
The article deals with the problem of content of students' readiness to the using of dialogue in educational process. Researching results show its influence on the effectiveness of dialogue education.